O turismo e a apropriação dos recursos naturais nas localidades receptoras – o caso da praia de Cabuçu, Saubara - BA - Barretto, Marcia Maria da Silva (2024)
In recent years, tourism has become one of the fastest growing economic activities in the world, consuming large portions of space, reshaping social relations and introducing numerous environmental problems in the receiving centers. Given these assumptions, an analysis of the environmental implications generated by tourism activity on the beaches of Cabuçu/BA becomes quite relevant. It is from this perspective that the central question of the research is to analyze tourism practice and its environmental implications on the beaches of Cabuçu over the last 40 years, reflecting on the role of state and municipal government in terms of its planning and monitoring. Specifically, the aim was to understand how the appropriation of the district's beaches by tourism activity occurred over the last four decades; to analyze how state and municipal government has planned and committed to the management of local tourism; and to verify the impressions of tent owners, vacationers and visitors about the environmental implications on the beaches resulting from tourism practice. Through publications that present the theme of tourism, documents prepared by federal, state and municipal agencies, field visits and questionnaires and semistructured interviews, it was possible to observe the removal and irregular occupation of restinga vegetation for residential and commercial constructions; the compaction of soil for anthropic buildings and the incorrect disposal of solid and liquid waste in rivers and the sea, generating impacts on the environment in the locality, which demonstrates the commercial use of physical spaces by the introduction of tourism, with the purpose of serving the capitalist logic. In view of this scenario, it is essential that actions be adopted capable of minimizing the environmental impacts on the beaches of Cabuçu, not as a solution to all the environmental problems present in the tourist center, but as a possibility to mitigate the negative effects on the natural environment, drawing attention to the rational use of natural resources.